An Evaluation of CD4 count in HIV patient: Bhayangkara Samsoeri Hospital - Budi Prasetyo Utomo; Oki Nugraha Putra; Ruddy Hartono (JOURNAL OF PHARMACY SCIENCE AND TECHNOLOGY, 2022)
HIV is an immune system disorder that characterized by a decreased CD4 count. The CD4 count in HIV patient is fluctuating, clinical conditions and opportunistic infections can affect the CD4 count. This study aims to determine antiretroviral to CD4 cell count in HIV patients with opportunistic infection who are outpatient at Bhayangkara HS Samsoeri Mertojoso Hospital Surabaya. The research design used was an analytical cross sectional observational using paired t-test. The main modality for HIV patients is fixed dose combination antiretroviral tablets. Observations on CD4 cell counts were carried out after the patient had taken antiretroviral combination tablets for a period of 12 months. The result of the study is, only 3 of 18 patients showed progresiion of CD4 cell counts. The conclusion in this study was that there was no significant difference between the mycosis group and the non-mycosis group (p> 0,05).